The Role of Grammatical Gender and Gender Stereotypes in Noun Processing: The Tug of War in Greek - Despoina Chalyvidou; Andrea Weber (Social Psychological Bulletin)
The present study examined the interaction of grammatical gender and gender stereotypes in Modern Greek. Native Greek adults were primed with Greek occupational nouns of common gender (i.e., nouns that are used for both male and female characters) with a masculine ending and a stereotypically male or female bias (e.g., iδravlikós ‘plumber’ and esθitikós ‘beautician’), followed by a masculine or feminine pronoun target (aftós ‘he’ or aftí ‘she’), forming stereotypically congruent (iδravlikós – aftós, ‘plumber – he’, esθitikós – aftí, ‘beautician - she’) and incongruent (iδravlikós – aftí, ‘plumber – she’, esθitikós – aftós, ‘beautician - he’) prime-target pairs. The participants’ task was to decide the gender of the pronoun, and their response times were measured. An effect of congruency was found for masculine pronouns, with slower response times when the masculine pronoun had been primed with a stereotypically female role noun. No such effect of congruency was found for feminine pronouns. This suggests that not only gender stereotypicality but also the morphological form of the noun influenced processing in Greek role nouns. Specifically, apparent morphosyntactic cues, albeit being uninformative about referential gender, seemingly generated a male bias and mitigated the impact of gender stereotypes associated with female-biased role nouns in prime-target pairs involving a feminine pronoun, reflecting an interaction between grammatical form and stereotype.